2018
DOI: 10.13005/ojc/340233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity 1-Monolaurin

Abstract: An improvement of method for synthesizing 1-monolaurin from lauric acid and glycerol has been done. The reaction was carried on mol ratio between lauric acid and glycerol 1:1 at 130 °C for 6 h with variation of pTSA catalyst of 2.5%, 5%, 7.5% (w/w of lauric acid). The purification of 1-monolaurin was conducted only by extracting with alcoholic solution. The product of 1-monolaurin was obtained as a white solid with 100% of purity from variation of 2.5% and 5% of pTSA catalyst with 43.54% and 27.89% yield, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…From these results, monomyristin showed better antibacterial and antifungal activities compared to monopalmitin. This is probably due to the shorter carbon chain near the monolauric acid [18]. The 1-position showed high activity for both antibacterial and antifungal agent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From these results, monomyristin showed better antibacterial and antifungal activities compared to monopalmitin. This is probably due to the shorter carbon chain near the monolauric acid [18]. The 1-position showed high activity for both antibacterial and antifungal agent.…”
Section: Resultsmentioning
confidence: 99%
“…Monoacylglycerol can be prepared through selective glycerolysis by using an inorganic base catalyst under a nitrogen atmosphere [14]. Lauric acid and monocaprin have been investigated as intravaginal microbicides to correct sexually transmitted diseases [15,16]. In our previous work, the 1-monolaurin compound was prepared in a simple and efficient method from lauric acid and glycerol in the presence of p -toluenesulfonic acid as the catalyst [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this transesterification reaction, alcohol is derived from 1,2-acetonide glycerol. For example, the reaction of fatty acids ethyl ester from ethyl capric with 1,2-acetonide glycerol using Na 2 CO 3 as a catalyst will produce 1,2-acetonide-3-capryl glycerol compound 78 . Usually, the transesterification of fatty acids ethyl ester ethyl capric 18 , ethyl myristic 19 with 1,2-acetonide glycerol took place at 110 for approximately 24 hours.…”
Section: Protected Glycerol In the Synthesis Of Monoglyceridesmentioning
confidence: 99%
“…The results of the analysis with Gas Chromatography showed that the 1-monolinolein product produced was cis-monolinolein 41.3 purity and trans-monolinolein 41.93 purity 32 . Deprotection reactions of 1,2-acetonide-3-alkyl glycerol can take place at room temperature for 24 hours using Amberlyst-15 in methanol 12 and ethanol 78 . The deprotection reaction in ethanol solvents is more advantageous because it can avoid the toxicity of the monoglyceride compounds produced.…”
Section: Protected Glycerol In the Synthesis Of Monoglyceridesmentioning
confidence: 99%